Reviews - Philip Barker; Andrea Frank; Chris Jones; Elaine Pearson; Gillian Jordan; John Traxler; Linda Clark (Association for Learning Technology, 2001)
The theme of this year's International Simulation and Gaming Yearbook - 'Transition and Change' - addresses the topical discourse on the improvement of pedagogy by the introduction of active and student-centred learning in UK higher education. Although the value of 'learning-by-doing' and experiential learning is well recognized by researchers in education, many subjects and university courses continue to employ teaching methods (such as lectures) that favour a passive reproduction of information rather than the fostering of student understanding. In this regard, simulations and games are powerful tools that not only promote an active, student-centred approach to learning but have the potential to help realize government policies to improve the quality of teaching and learning in higher education institutions in the UK.